Examining consumer purchase intentions of non‐prescription medicines in supermarkets and community pharmacies. (15th November 2018) - Mortimer, Gary; Grimmer, Louise; Fazal‐e‐Hasan, Syed M.
Abstract: Objective: As supermarkets continue to expand their healthcare categories, consumers now have more choice and access to non‐prescription medicines. The aim of this current research is to empirically examine the drivers and barriers of consumer purchase intentions, namely trust and perceived risk, of non‐prescription medicines in both supermarkets and community pharmacy settings. Method: Data were collected using an in‐store intercept survey of 402 supermarket shoppers and 310 community pharmacy shoppers. Confirmatory factor analysis including a measurement and structural model tests were employed using AMOS software package to identify variances in the drivers and barriers of purchase intentions between these retail settings. Key findings: This study found an association between the purchase intention of non‐prescription medicines in community pharmacies with their perceived competence, benevolence and provision accurate information . Other than time risk, no other elements of risk were associated with purchase intentions within this setting. In contrast, the perceived risks associated with the purchase of non‐prescription medicines within the supermarkets setting – specifically physical and social risk, were present. Results indicate respondents were more likely to intend to purchase medicines from a supermarket if they perceived that the retailer was competent in providing access to safe non‐prescription medicines and had the ability to handle transactions. Conclusions: This is the first study to examine the psychological drivers and barriers of purchase intentions of non‐prescription medicines in supermarkets and community pharmacies, finding very different results across both retail settings. The study presents a comprehensive model of purchase intentions of non‐prescription medicines and recommends directions for pharmacy practitioners and supermarkets.